2021
DOI: 10.1038/s41419-021-04259-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting microcephaly genes as alternative to microtubule targeting agents to treat brain tumors

Abstract: Medulloblastoma (MB) and gliomas are the most frequent high-grade brain tumors (HGBT) in children and adulthood, respectively. The general treatment for these tumors consists in surgery, followed by radiotherapy and chemotherapy. Despite the improvement in patient survival, these therapies are only partially effective, and many patients still die. In the last decades, microtubules have emerged as interesting molecular targets for HGBT, as various microtubule targeting agents (MTAs) have been developed and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 142 publications
(221 reference statements)
2
12
0
Order By: Relevance
“…Targeting of microcephaly-associated genes has been proposed as an alternative to microtubule-targeting agents to treat brain tumors (Iegiani et al, 2021). In line with this idea, our results…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Targeting of microcephaly-associated genes has been proposed as an alternative to microtubule-targeting agents to treat brain tumors (Iegiani et al, 2021). In line with this idea, our results…”
Section: Discussionsupporting
confidence: 87%
“…Targeting of microcephaly-associated genes has been proposed as an alternative to microtubule-targeting agents to treat brain tumors (Iegiani et al, 2021). In line with this idea, our results showed that MAGOH and MAGOHB knockdown is well-tolerated in astrocytes but not in GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high expression of ASPM correlated directly with chromosome missegregation and increased numbers of micronuclei, suggesting that high expression of ASPM in NSCLC is more likely to be intrinsic and integral to RT resistance rather than incidental. This notion is also supported by recent comprehensive functional analyses of ASPM in different types of tumors in patients [39][40][41]. We propose that mis-segregation of chromosomes could have much broader effects extending beyond radiation resistance in cancer, which underscores the broad clinical value of understanding the exact role of the genomic instability in cancer progression and therapy.…”
Section: Discussionsupporting
confidence: 63%
“…Consequently, nonviral gene therapy presents an attractive, low‐cost alternative to current standards of care, especially as new biological mechanisms can be targeted. Beyond delivery of cytotoxic genes, some examples of additional nonviral gene therapy approaches with mechanisms that can suppress brain tumors include nanoparticles delivering miR‐486‐5p antagomirs or cancer inhibiting miRNAs (Lopez‐Bertoni et al, 2018, 2020), delivering factors such as bone morphogenetic proteins to inhibit cancer cell stem cells (Piccirillo et al, 2006), or targeting microcephaly genes (Iegiani et al, 2021).…”
Section: Central Nervous System Anatomy and Common Neurological Disea...mentioning
confidence: 99%